The role of "open" in strategic library planning - Petrides, Lisa; Goger, Letha; Jimes, Cynthia (Education Policy Analysis Archives, 2016)
Academic libraries are undergoing evolutionary change as emerging technologies and new philosophies about how information is created, distributed, and shared have disrupted traditional operations and services. Additionally, the population that the academic library serves is increasingly distributed due to distance learning opportunities and new models of teaching and learning. This article, the first in this special issue, suggests that in today’s increasingly networked and distributed information environment, the strategic integration of open curation and collection development practices can serve as a useful means for organizing and providing structure to the diverse mass of available digital information, so that individual users of the library have access to coherent contexts for meaningful engagement with that information. Building on insights from extant research and practice, this article proposes that colleges and universities recognize a more inclusive open access environment, including the integration of resources outside of those owned or created by the institution, and a shift toward policies that consider open access research and open educational resources as part of the library’s formal curatorial workflow and collection building. At the conclusion on this article, authors Lisa Petrides and Cynthia Jimes offer a commentary on the six remaining articles that comprise this special issue on Models of Open Education in Higher Education, discussing the significant role that “open” policy and practice play in shaping teaching, learning, and scholarship in the global context of higher education.